STRUKTURE AND COMPOSITION OF INFORMATION BASIS OF AUTOMATED SYNTESIS OF THE ROBOTIC MECHANICAL ASSEMBLING TECHNOLOGIES - Vygovskyy, G.; Gromovyy, O.; Kyrylovych, V.; Kryzhanivska, I. (Енергетика і автоматика, 2016)
Input information is the result of the preceding stages of flexible manufacturing cells (FMC) design and synthesis technology in them.Thatinput information is considered as an information basis (base) that influences and determines the content, structure and parameters of intermediate and final information.All incoming information is seen as permanent, relatively constant and variable. There are disclosed the essence of these components of the input data, its origin and source location. There are defined the place of the previously developed the informational models of the components of known technical basis of FMC which are invariant relatively a formulation of the automated synthesis of robotic mechanical assembling technologies (AS RMAT) setting tasks.There dused scheme with the composition and the structure of the information basis clearly illustrates its components and the relationships between them.The feature of the descriptions of information basis components is the theory of quaternions, the only meaningful units which make it possible in furtherto makethe systematic technological solutions in the formation of intermediate and final information AS RMAT.